Invariant Point Theorems in Partially ordered Soft Metric-like Spaces - et. al, Sneha A. Khandait (International Journal of Control and Automation, 2019)
In this paper an idea of partially soft metric space is introduced and also some fixed point theorems involving weakly contractive mapping defined in partially ordered soft metric-like space are established. Obtained results, even in case of partial soft metric spaces generalized form of some well-known results from partially ordered metric like spaces.